Seleção de áreas potenciais para implantação da zona de processamento e exportação de Fernandópolis - SP utilizando geotecnologia - Moraes, Igor Amedi de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The implementation of an Export and Processing Zone (ZEPs) brings several benefits to the local, state and federal economy, but often, only socioeconomic factors are considered, apart from several other factors that should be analyzed, such as the environment. In this context of industrialization and the struggle for sustainable development, this work propose to incorporate the environmental variable in the decision process for establishing industrial areas, in particular, the ZPE in the city of Fernandópolis, São Paulo state, Brazil, by examining several physical and environmental factors such as slope intervals, geological features, pedological factors and land use. Developed using a multicriteria analysis, a model has been elaborated, where these factors have received a proportional value according with their importance, supported by a GIS tool (Geographical Information System) and remote sensing products, such as images from CBERS satellite and SRTM radar, showing the suited areas for industrial activities, considering environmental conditions. This model may assist to take better decision about the ZPE implementation area and to reduce the negative environmental impacts that would result of poorly planned locations

Os benefícios resultantes da implantação de uma Zona de Processamento e Exportação (ZEPs) são muitos, abrangendo os níveis local, estadual e federal, mas muitas vezes somente os fatores socioeconômicos são levados em consideração, deixando de lado diversos outros fatores que deveriam ser analisados, como o meio ambiente. Neste contexto de industrialização e a luta pelo desenvolvimento sustentável, o presente trabalho visa incorporar a variável ambiental no processo de decisão de áreas de locação industrial, em especial, a ZPE da cidade de Fernandópolis – SP, analisando fatores físicos e ambientais como, classes de declividade, características geológica, características pedológica, e uso da terra. Seguindo uma análise multicritério de ponderação destes fatores, auxiliado por ferramenta SIG (Sistema de Informação Geográfica), e produtos de sensoriamento remoto, como imagens do satélite CBERS e imagem SRTM, foi feita uma modelagem demonstrando as áreas de melhor aptidão para as atividades industriais, podendo auxiliar e reduzir os impactos negativos no meio ambiente que adviriam do fruto de locações mal planejadas
Keywords: Engenharia ambiental; Geografia - Programas de computador; Sensoriamento remoto; Fernandopolis (SP)